Implementation Of Virtual Tours Usingweb-Based 360° Panoramas At The Faculty Of Engineering, University Of Islam Riau - Selvia Margareta Sitompul; Octadino Haryadi (Yayasan Ibrahim Learning Centre Agam, 2025)
The development of digital technology has opened up great opportunities for delivering campus information virtually. This study aims to develop and implement a 360° panorama-based virtual tour system at the Faculty of Engineering, Riau Islamic University, to provide an interactive overview to prospective students and the general public without having to visit the location directly. This system was developed using the Multimedia Development Life Cycle (MDLC) method, which consists of six stages: Concept, Design, Material Collecting, Assembly, Testing, and Distribution. The results of the study show that this web-based virtual tour system is capable of displaying various campus facilities, such as buildings, laboratories, halls, and lecturer rooms virtually. Evaluation using the Black Box method and questionnaires to users provided positive results, with the majority of respondents feeling helped and satisfied with the information conveyed through the system. It is hoped that this system will become an effective and efficient digital promotion and information medium for the Faculty of Engineering at UIR.